A Case of Post COVID-19 Subacute Thyroiditis - Khan Mark, Sayeef Hossain; Mishu, Shaima Rahman; Khan, Rasif Hossain; Mozammel, Warda; Kalam Azad, Khan Abul (Bangladesh Journal of Medicine, 2022)
Subacute thyroiditis is an immune reaction of the thyroid gland that often follows an upper respiratory tract infection. It is an uncommon but usually a self-limiting inflammatory condition. The clinical presentation varies from person to person, but usually includes neck pain or discomfort and a painful diffuse goiter. There is at times a transient episode of hyperthyroidism followed by euthyroidism and sometimes hypothyroidism. We describe the case of a previously healthy 34- year-old female presenting with symptoms consistent with subacute thyroiditis. The patient had recently recovered from a mild episode of COVID-19 infection. Labs and imaging were consistent with the clinical diagnosis of subacute thyroiditis. The patient was provided symptomatic treatment with prednisone and propranolol and had an uneventful recovery. Bangladesh J Medicine 2022; 33: 210-212